Effect of Pretreatment and C/N Ratio in Anaerobic Digestion on Biogas Production from Coffee Grounds and Rice Husk Mixtures - Budiyono Budiyono; Hashfi Hawali Abdul Matin; Ihzani Yulistra Yasmin; Iwang Septo Priogo (International Journal of Renewable Energy Development, 2023)
Indonesia has great potential in producing large quantities of renewable energy sources, such as biomass. Biogas is a renewable energy source produced from biomass. It is can be developed in agricultural countries producing rice and coffee, where a large amount of waste is produced in the form of rice husks and coffee grounds. This study examined the effect of physiochemical pretreatment and the C/N ratio on biogas production using coffee grounds and rice husk mixtures. Physical pretreatment was conducted by grinding the mixture up to 50 mesh size, followed by chemical pretreatment by soaking the mixture in 3% KOH; moreover, the variation in the C/N ratio was set at 25 and 30. Anaerobic bacteria were acquired from rumen fluid. The ratio of the coffee ground material, rice husks, and rumen fluid was 1:1:1. This research was conducted in duplicate under batch conditions at ambient temperature (25–35 oC) with a digester volume of 1.5 L. Biogas productivity was measured every 2 d for 60 d. The experimental results indicated that biogas production with a C/N ratio of 30 was 13.3–66.5% higher than that with a C/N ratio of 25. The inclusion of physical pretreatment at a C/N ratio of 30 increased biogas production by up to 31.3%. Moreover, the inclusion of a chemical pretreatment at a C/N ratio of 30 resulted in 30.3% higher biogas production. The kinetics model of biogas production showed that a C/N ratio of 30 with physical and alkaline pretreatment can produce maximum biogas yields of 6,619 mL and 6,570 mL, respectively. Overall, both pretreatments sequentially increased the biogas production significantly.